Beyond sight enhancing human echolocation for the visually impaired through the development of urban public spaces - Ponce, Joyceleigh C. (College of Architecture, University of the Philippines Diliman, 2015)
To realize the full potential of human, different cultural and intellectual movements such as transhumanism arise. Transhumanism is about finding solutions to modify human conditions through various biological and technological means. Different studies show how the surrounding environment greatly contributes to this development as it enables human senses to work. Still, the interaction is elusive when individuals lack certain senses to fully understand their environment, which compel them to rely on a specific sense. Most visually impaired individuals perceive their environment as series of images created in their mind based on what they hear. Echolocation is a rudimentary perception-action ability of humans, but it is difficult for humans to perceive objects at short distances because sounds and echoes are subjectively blurry. Although this ability is not innate, people can learn how to echolocate if they are exposed in a proper setting. One important factor which makes it difficult to perform echolocation is noise coming from the surrounding environment, especially in urban public spaces with high level of noise pollution created by busy streets and different human activities. With this, the study aims to develop urban public spaces so that it can be amenable for echolocation. It also aims to program an urban landscape design that will mask the noise through the use of different landscape architecture elements and strategic spatial planning. This is achieved through a unique research design which includes experimental activities with blind and low vision participants in order to gather information about how they interact with their surroundings. Through different activities such as Accompanied Walks, Word Game and Mental Mapping, information such as positive and negative urban elements as viewed by visually impaired are gathered. The results are then integrated with the sound analysis of the sites to create spaces that will not only benefit the visually impaired, but can also be enjoyed by all. By being exposed to these multisensory spaces every day, it can improve the overall capabilities of visually impaired individuals and encourage them to go out and experience the outdoor environment with confidence.